(untitled) (Eurasian Journal of Learning and Academic Teaching, 2022)
This article describes the concept of certain categories of employees, labor disputes arising in the process of their reinstatement, the jurisdiction of labor disputes involving them, as well as errors and omissions in the practice of resolving labor disputes by the courts, suggestions and conclusions for their legal resolution